2004
DOI: 10.1523/jneurosci.1988-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Early N-Terminal Changes and Caspase-6 Cleavage of Tau in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is a progressive amnestic dementia that involves post-translational hyperphosphorylation, enzymatic cleavage, and conformational alterations of the microtubule-associated protein tau. The truncation state of tau influences many of its pathologic characteristics, including its ability to assume AD-related conformations and to assemble into filaments. Cleavage also appears to be an important marker in AD progression. Although C-terminal truncation of tau at D421 has recently been attribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
179
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(186 citation statements)
references
References 51 publications
7
179
0
Order By: Relevance
“…It is possible that a substantial phosphorylation of Y18 and/or Y29 occurs primarily at later stages of neurofibrillary tangle formation than those observed in the JNPL3 we examined. In this regard, it has been reported that antibodies to tau peptides phosphorylated at Y18 (aa 12-24) recognize fewer tangles in AD brain than those unphosphorylated tau peptides (aa , and that compact fibrillary tangles, but not early diffuse tangles, display phosphorylated Y18 immunoreactivity [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that a substantial phosphorylation of Y18 and/or Y29 occurs primarily at later stages of neurofibrillary tangle formation than those observed in the JNPL3 we examined. In this regard, it has been reported that antibodies to tau peptides phosphorylated at Y18 (aa 12-24) recognize fewer tangles in AD brain than those unphosphorylated tau peptides (aa , and that compact fibrillary tangles, but not early diffuse tangles, display phosphorylated Y18 immunoreactivity [8].…”
Section: Discussionmentioning
confidence: 99%
“…Yen's laboratory [4]], monoclonal Tau12 [aa 9-18; 1:20000; provided by Dr. Lester Binder [8]], and phospho-tau-specific antibodies CP13 (S202 and T205) and PHF-1 (S396 and S404) (both provided by Dr. Peter Davies [6], 1:1000); monoclonal phospho-tyrosine-specific 4G10 antibody (Upstate, NY) (1:200). Secondary antibodies used in Western blot analysis are as follows: peroxidase-conjugated goat anti-rabbit (1:4000) or goat anti-mouse (1:2000) Ig antibodies (Chemicon, Temecula, CA, USA).…”
Section: Antibodiesmentioning
confidence: 99%
“…Although caspase-3 seems to be the primary caspase in this case, colocalization with intracellular tau inclusions, in the form of neurophil threads and neurofibrillary tangles, and site-specific processing of tau protein also implicate caspase-6 in this process. 76,77 Moreover, accumulated caspase cleavage-mediated huntingtin fragments represent an early pathological change in the brains of Huntington's disease patients. Using a Huntington's disease mouse model that develops Huntington's-related characteristics with age, it was shown that individuals expressing a mutant huntingtin protein, which is resistant to caspase-6 cleavage, are protected from neuronal dysfunction.…”
Section: Caspases and Cancer M Olsson And B Zhivotovskymentioning
confidence: 99%
“…It has been shown that truncation is closely associated with Alzheimer's disease (AD)-typical conformational changes of the tau protein [5][6][7][8][9][10]. We have hypothesized that truncation could play major role in AD tau pathology [11].…”
Section: Introductionmentioning
confidence: 99%